2003
DOI: 10.1063/1.1557653
|View full text |Cite
|
Sign up to set email alerts
|

Influence of underlayers on the soft properties of high magnetization FeCo films

Abstract: A remarkable reduction in coercivity Hc was found in sputtered Fe65Co35(=FeCo) films on Cu, NiFe, Ru, Ta/Cu, Ta/NiFe, or Cu/IrMn underlayers. A decrease in Hc from 120 to 7–12 Oe was observed for Cu, NiFe, and Ru underlayers as thin as 2.5 nm but less for Ta. A Cu underlayer significantly reduced the maximum anisotropy fields from 2 kOe to 40 Oe, resulting in a well-defined in-plane average uniaxial anisotropy field Hk∼30 Oe. The saturation magnetostriction with Cu was (47±4)×10−6, independent of Cu and FeCo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
49
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 11 publications
(10 reference statements)
8
49
1
1
Order By: Relevance
“…This texture change might result in stress relief [17]. So, our results are similar with recent studies which reveal that texture change in crystal structure accompanies coercivity reduction [3,9,11,12,15]. Overall, according to GI-XRD results, it is not hard to say that film texture is tailored by underlayers.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This texture change might result in stress relief [17]. So, our results are similar with recent studies which reveal that texture change in crystal structure accompanies coercivity reduction [3,9,11,12,15]. Overall, according to GI-XRD results, it is not hard to say that film texture is tailored by underlayers.…”
Section: Resultssupporting
confidence: 80%
“…Much effort has done for lowering coercivity of FeCo alloys to improve soft magnetic properties in recent years. Underlayers, adding additives, and using different deposition techniques are frequently used methods for lowering coercivity [4,5,[8][9][10][11][12]. The reduction of coercivity in these studies generally suggested that consequence of reducing grain size according to Hoffman's ripple theory or change on preferred crystal orientation [4,8,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that samples A1 and A2 with small grain size are magnetically soft and in-plane anisotropic, while samples B1 and B2 with large grains are magnetically harder with coercivities exceeding 120 Oe. These samples are in-plane isotropic [1]. The observed change in the coercivity with grain size is in agreement with the random anisotropy model [5], [6].…”
Section: Resultssupporting
confidence: 70%
“…Controlling both and of CoFe is difficult and usually involves the use of additives or seed layers [1], which are inconvenient in terms of cost and final device capabilities. In this paper, we demonstrate the preparation of CoFe thin films with control of and over a broad range of values.…”
Section: Introductionmentioning
confidence: 99%